Author-readers of literary tradition: digital literature as a preservational action - Gobira, Pablo (2019)
This work aims to identify and analyze digital literary artworks in which the notions of author and reader approach narrative and poetic experiences based on appropriations of texts from the literary tradition. This approach is based on the composition of digital literary artworks, in which the act of "reading", in the relations between literature and technology, can also mean a way of preserving tradition, when it rebuilds it to advance it, repeating – many times. sometimes even through reader interactivity – a way of reviving the literary text differently. We discuss, in the article, the digital artworks: Jhave's MUPs (2013), Scot Gresham-Lancaster and Tim Perkis's iLib Shakespeare (2014); and Alan Bigelow's MyNovel (2006). These artworks were selected from the Turbulence digital repository, which will allow us to illustrate the redemption of tradition through the aesthetic development of artworks, constituting this “author-reader” who acts together for the composition of the digital artwork.